2D tomographic inversion of complex resistivity data on cylindrical models. (6th March 2013) - De Donno, Giorgio
ABSTRACT: The resistive and capacitive response of a multiphase subsoil can be analysed by amplitude and phase models of the electrical complex resistivity. The main goal of this work is to extend the 2D transformed formulation used for electrical site investigations for cylindrical laboratory models, solving the complex resistivity forward problem starting from the Complete Electrode Model approach. This formulation is tested by a comparison with the full 3D solution and is proven to be stable and accurate. Inversion of complex resistivity data is achieved through a Matlab interface included in the EIDORS environment, with the addition of numerous new functions. Three synthetic examples are discussed, to understand the potential and limits of this approach in comparison with the 3D inversion. Laboratory experiments on a cylindrical laboratory model with a horizontal cross‐section of 10 electrodes validated synthetic results. The model having a height of 1 m and a diameter of 500 mm is made by sand contaminated from the top by an engineered fluid with electrical properties similar to chlorinated solvents.